Fiscal and monetary policy determinants of the Eurozone crisis and its resolution - Marek Dabrowski (Center for Social and Economic Research (CASE), 2012)
Unlike the crisis years of 2007-2009 (when the insolvency of large banks was a major problem), the current round of the global financial crisis has fiscal origins. Almost all developed countries suffer from an excessive public debt burden that has been built up over the last two decades or more. The financial crisis caused a further deterioration of government accounts as a result of ill-tailored countercyclical fiscal response and, in some cases, a costly financial sector rescue. All excessively indebted countries must conduct fiscal adjustment, even if this involves economic and political costs in terms of lower output and higher unemployment. Central banks can reduce these costs through accommodative monetary policies but without compromising their anti-inflationary missions and institutional independence. The ECB is additionally constrained by its institutional status which is based on a delicate cross-country political consensus. Excessive ECB involvement in quasi-fiscal rescue operations can undermine this consensus and lead to a disintegration of the Eurozone. There are also strong arguments in favor of strengthening fiscal and banking integration within the EU, especially the fiscal discipline mechanism at national levels, and building the EU rescue capacity in respect to sovereigns and banks based on strong policy conditionality.
Keywords: E58; E62; E63; F33; F34; F36; G01; H62; H63; 330; Financial crisis; Sovereign debt crisis; Fiscal adjustment; European Union; Economic and Monetary Union; Eurozone; Maastricht Treaty; European Central Bank; Euro; Fiscal union; Finanzkrise; Schuldenkrise; Finanzpolitik; Geldpolitik; Konvergenzkriterien; Europäischer Stabilitätsmechanismus; Eurozone; EU-Staaten